Angiopoietin 2 Levels in the Risk Stratification and Mortality Outcome Prediction of Sepsis-Associated Coagulopathy. (November 2018) - Statz, Stephen; Sabal, Giselle; Walborn, Amanda; Williams, Mark; Hoppensteadt, Debra; Mosier, Michael; Rondina, Matthew; Fareed, Jawed
It has been well established that angiopoietin 2 (Ang-2), a glycoprotein involved in activation of the endothelium, plays an integral role in the pathophysiology of sepsis and many other inflammatory conditions. However, the role of Ang-2 in sepsis-associated coagulopathy (SAC) specifically has not been defined. The aim of this study was to measure Ang-2 plasma levels in patients with sepsis and suspected disseminated intravascular coagulation (DIC) in order to demonstrate its predictive value in SAC severity determination and 28-day mortality outcome. Plasma samples were collected from 102 patients with sepsis and suspected DIC at intensive care unit (ICU) admission. The Ang-2 plasma levels were quantified using a sandwich enzyme-linked immunosorbent assay method. The International Society on Thrombosis and Haemostasis DIC scoring system was used to compare the accuracy of Ang-2 levels versus clinical illness severity scores in predicting SAC severity. Mean Ang-2 levels in patients with sepsis and DIC were significantly higher in comparison to healthy controls ( P < 0.0001), and median Ang-2 levels showed a downward trend over time ( P = 0.0008). Baseline Ang-2 levels and clinical illness severity scores were higher with increasing severity of disease, and Ang-2 was a better predictor of DIC severity than clinical illness scores. This study demonstrates that Ang-2 levels are significantly upregulated in SAC, and this biomarker can be used to risk stratify patients with sepsis into non-overt DIC and overt DIC. Furthermore, the Ang-2 level at ICU admission in a patient with sepsis and suspected DIC may provide a predictive biomarker for mortality outcome.